The Value of Soil Knowledge in Understanding Wine Terroir - White, Robert E. (Frontiers in Environmental Science, 2020)
There is an extensive literature on the role of soil physicochemical factors such as rate of water supply, N supply and soil temperature in wine terroir expression, especially for dry-grown vines. Other recent literature invokes the possibility of unique strains of the yeast Saccharomyces cerevisiae influencing must fermentations to produce distinctive aroma profiles in wines. Others suggest that the composition of the soil microbiome at particular sites can influence vine growth, fruit composition and wine characteristics to create a microbial terroir. However, the lack of known quantitative relationships between any one or more of these variables and the expression of a site’s terroir over time limits a vigneron’s ability to manipulate vineyard management to meet a specific terroir objective.